Contamination of hospital tap water: the survival and persistence of Pseudomonas aeruginosa on conventional and 'antimicrobial' outlet fittings. Issue 2 (October 2017) - Hutchins, C.F.; Moore, G.; Thompson, K.-A.; Webb, J.; Walker, J.T.
Summary: Background: Pseudomonas aeruginosa infections have been linked to contaminated hospital taps, highlighting the potential for tap outlet fittings (OF) to harbour biofilm. P. aeruginosa may be transferred to OFs via contaminated cleaning cloths. Suggested interventions include flushing regimens and alternative OF designs. Aim: To investigate the transfer of P. aeruginosa from a contaminated cleaning cloth to conventional and 'antimicrobial/antibiofilm' OFs and to determine whether this contamination persists and/or leads to contamination of tap water. Methods: Microfibre cloths contaminated with P. aeruginosa (10 8  cfu/mL) were used to wipe four different types of OF [one of conventional design (OF-A) and three marketed as 'antimicrobial' and/or 'antibiofilm' (OF- B, -C and -D)]. OFs were inserted into an experimental water distribution system for up to 24 h. Survival was assessed by culture. Single and multiple water samples were collected and cultured for P. aeruginosa . Findings: The median number of P. aeruginosa transferred from cloth to OF was 5.7 × 10 5  cfu (OF-A), 1.9 × 10 6  cfu (OF-B), 1.4 × 10 5  cfu (OF-C) and 2.9 × 10 6  cfu (OF-D). Numbers declined on all OFs during the 24 h period with log reductions ranging from 3.5 (OF-C) to 5.2 (OF-B; P  > 0.05). All water samples delivered immediately after OF contamination contained P. aeruginosa at ≥10 cfu per 100 mL. Contamination of water delivered from OF-A persisted despite continued flushing. Water delivered from OF-B did not contain P. aeruginosa beyond the first flush. Conclusion: Contaminated cleaning cloths may transfer P. aeruginosa to OFs, leading to contamination of tap water. Although not removing the potential for contamination, 'antimicrobial/antibiofilm' OFs may prevent P. aeruginosa from continually contaminating water delivered from the outlet.